Association between high-heeled shoes of varied heel height and bladder neck elevation in women: an exploratory study. (4th May 2019) - Kannan, Priya; Fung, Brigitte; Leung, Regina W.C.; Goonetilleke, Ravindra; Winser, Stanley J.
Abstract : Objectives: To evaluate the relationship between high-heeled shoes of varied heel height and bladder neck elevation in women. Methods: A cross-sectional, exploratory design was applied. Twenty-three continent 18–49-year-old women performed pelvic floor muscle (PFM) contractions while standing in high-heeled shoes of varied heel height. Transabdominal ultrasound was used to evaluate bladder neck elevation in ventral-cranial direction from the resting position during maximum voluntary contraction (MVC) of pelvic floor muscles. Results: Significantly greater bladder neck elevation was demonstrated in neutral ankle position compared to the two- (0.27 [95% CI 0.14–0.39] p < 0.001) and three-inch high-heeled conditions (0.37 [95% CI 0.21–0.53]) p < 0.001). A non-significant association was found between lumbopelvic angle and bladder neck elevation in the ankle dorsiflexion and the two- and three-inch high-heeled conditions. Conclusion: S ignificantly lower bladder neck elevation in high-heeled conditions indicates that pelvic floor muscle contraction to elevate bladder neck might not be as strong while wearing high-heel shoes as it is while standing bare feet. Further studies with larger sample size are required to evaluate the possible relationship between varied heel height, bladder neck elevation, and urinary incontinence in women.